2014
DOI: 10.1097/rlu.0000000000000476
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Myofibroblastic Tumor of the Lung Indistinguishable From Adenocarcinoma on Imaging Studies

Abstract: We present the case of a right lung nodule discovered on routine chest x-ray in an asymptomatic 62-year-old man. CT revealed a spiculated nodule in segment 1 of the right upper lobe, 2.2 cm in diameter and without calcification. The nodule showed high focal FDG uptake (SUVmax, 17.8) on PET. Right upper lobectomy was performed under the diagnosis of adenocarcinoma; however, the histopathologic findings were of inflammatory myofibroblastic tumor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…peripheral, punctate or fine) are seen in 15% of IMTs. However, calcification is very rare in adult IMTs [ 12 ]. We observed three different manifestations of IMT, namely cavitation in case 1, densely calcified perihilar mass in case 2, and consolidative mass lesion in case 3.…”
Section: Discussionmentioning
confidence: 99%
“…peripheral, punctate or fine) are seen in 15% of IMTs. However, calcification is very rare in adult IMTs [ 12 ]. We observed three different manifestations of IMT, namely cavitation in case 1, densely calcified perihilar mass in case 2, and consolidative mass lesion in case 3.…”
Section: Discussionmentioning
confidence: 99%
“…A study based on next-generation sequencing (NGS) assays reported that two of nine ALKnegative patients harbored PDGFRβ kinase fusions, and four of them harbored ROS1 kinase fusions, suggesting that IMT is likely a kinase fusion-driven tumor (24). Clinically, it is very difficult to distinguish pulmonary IMT from lung cancer (25). The clinical manifestations of IMT are not specific.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, it is very difficult to distinguish pulmonary IMT from lung cancer ( 25 ). The clinical manifestations of IMT are not specific.…”
Section: Discussionmentioning
confidence: 99%
“…IMTs have been observed predominantly in young patients and have been encountered virtually in any anatomical location such as the lungs [2], mesentery [4], omentum [3], retroperitoneum [5], extremities [6], head [7], liver [10], spleen [11], thyroid [12], and urinary bladder [13]. Notably, reported cases on IMTs/IPTs of the breast are very scarce [1, 9, 14–34].…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory myofibroblastic tumors have largely been considered as a subgroup of inflammatory pseudotumors [1] and have been encountered in various anatomical locations [27]. Interestingly, mammary IMTs have scarcely been reported.…”
Section: Introductionmentioning
confidence: 99%